Transition Rate Of Girls From Lower Primary To Upper Primary, Kajiado County - Nyagah, S. N.; Luketero, S.W. (European Scientific Journal, ESJ, 2016)
This study is on factors that influence the girls’ transition rate from lower primary to upper primary in public primary schools of Kajiado County, Kenya. Four study questions guided the study. Literature review focused on international calls on girl’s education among the pastoral communities and the girl’s education in Kenya and Africa at large. The study focused on the factors that influence girls’ education which include the socio-cultural factors, socio-economic factors, school based factors and early teenage pregnancies which include the flight of the girls due to the effects of HIV/AIDS and FGM. The study used the descriptive survey design. The target population for the study was 524 comprising of 14 head teachers and 510 class six girls from all the fourteen public primary schools in Kajiado County. The sample for the study was 14 head teachers, and 16% of the girls (82) in class six from the selected schools. Based on the findings the following conclusions were made: Early marriage was found to be the main cause of girls not graduating to the next higher level of education in public primary schools. Female genital mutilation (FGM) was the second contributing factor to low transition rate of girls. Results on physical facilities had mixed reactions. Majority of the girls (72.5%) belief that lack of physical facilities had no influence on them being or not being in school. This meant that whether the physical facilities are available or not the girls will still continue with their education. Early pregnancies represented by 88.4% most likely to lead to girls leaving school before completing the entire primary cycle. Only 8.7% of the respondents indicated that early pregnancy had no influence on girls being or not being in school. It was found that there was high percentage of girls out of school due to lack of female teachers in their school to act as role models. The study also established that most of the girls from poor households go through FGM as compared to those from rich households, in which case FGM will lead to early pregnancies hence the girl leaving school.